Examining the impact of psychological contract on the relationship between HSE culture and citizenship behavior in the steel industry - Abouzar Amirian; Davood Afshari; Leila Omidi; Maryam Seyedtabib; Maryam Nourollahi-Darabad (بهداشت و ایمنی کار)
Introduction: Nowadays, in order to improve the level of Health, Safety and Environment (HSE) culture of employees, organizations have reached this important conclusion that the weaknesses and strengths of the system should be identified by periodically evaluating the level of HSE culture. On the other hand, Although the social exchange relationships between employers and employees are increasingly important to the performance of safety management systems, the interaction between psychological aspects, workplace safety and its relationship with employees’ HSE citizenship behavior have been less studied. The aim of the present study was to investigate the effect of psychological contract of HSE on the relationship between HSE culture and HSE citizenship behavior among employees in a steel manufacturing industry. Material and Methods: In the present study, three questionnaires: Psychological contract of HSE, HSE citizenship behavior and HSE culture were used; the reliability and validity of these questionnaires approved in past studies. The questionnaires were randomly distributed to 434 employees of a steel industry. In order to model structural equations, Smart PLS software was used, the reliability and validity of the models were investigated. Results: The results of the study showed that HSE culture is a significant predictor of HSE citizenship behavior (P-value<0.001). HSE culture has a positive and significant effect on psychological contract (P-value <0.001), and psychological contract has a mediating role in the relationship between HSE culture and HSE citizenship behavior. Conclusion: The results of the present study showed that HSE culture and psychological contract directly affect HSE citizenship behavior. Also, based on the findings of this study, HSE culture, in addition to directly affecting HSE citizenship behavior, can also affect HSE citizenship behavior by affecting psychological contract as a mediating variable.